Ocean acidification and kelp development Reduced pH has no negative effects on meiospore germination and gametophyte development of Macrocystis pyrifera and Undaria pinnatifida - Leal, Pablo P (Journal of phycology, 2017)
© 2017 Phycological Society of America.